PLS Finance and Monetary Policy: A New Measure Mooted - Hasan, Zubair (Journal of Reviews on Global Economics, 2016)
Islam banishes interest. This raises two questions contextual to Central Banking. First, can Islamic banks create credit like the conventional? We shall argue that Islamic banks cannot avoid credit creation; an imperative for staying in the market where they operate in competition with their conventional rivals. Evidently, the interest rate policy would not be applicable to them as a control measure. This leads us to the second question: What could possibly replace the interest rate for Islamic banks? In reply, the paper suggests what it calls a leverage control rate (LCR) as an addition to Central Banks' credit control arsenal. The proposed rate is derived from the sharing of profit ratio in Islamic banking. It is contended that the new measure has an edge over the old fashioned interest rate instrument which it can in fact replace with advantage. It can possibly be a common measure in a dual system.